Evidence for a Selectively Regulated Prioritization Shift Depending on Walking Situations in Older Adults - Salkovic, Dina; Hobert, Markus A.; Bellut, Carolin; Funer, Florian; Renno, Sarah; Haertner, Linda; Hasmann, Sandra E.; Staebler, Jana; Geritz, Johanna; Suenkel, Ulrike; Fallgatter, Andreas J.; Eschweiler, Gerhard W.; et al. (Frontiers in Aging Neuroscience, 2017)
Abstract Background: Older adults have increased risks of balance issues and falls when walking and performing turns in daily situations. Changes of prioritization during different walking situations associated with dual tasking may contribute to these deficits. The objective of this study was therefore to investigate whether older adults demonstrate changes of prioritization during different walking paths. Methods: In total, 1054 subjects with an age range from 50 to 83 years were selected from the first follow-up visit of the TREND (Tuebinger evaluation of Risk factors for Early detection of Neurodegenerative Disorders) study. They were classified according to their performance on the Trail Making Test (TMT) into good and poor TMT performers (based on recent results showing that cognitive flexibility affects prioritization strategies during straight walking). Absolute dual-task performance and relative dual-task costs (DTC, relative performance under dual-task conditions compared with single-task conditions) were assessed in two paradigms: walking while subtracting serial 7s and walking while checking boxes on a clipboard. Both tasks were performed on straight and curved paths. Results: Overall, the poor TMT performers group performed worse in all single and dual tasks. Interestingly, the relative change in performance measured by dual-task costs differed in the groups between the two walking paths. On straight paths, poor TMT performers had a similar DTC of walking to that of good performers (p=0.10) but had a significantly lower DTC of subtracting (p=0.02). On curved paths, poor performers had a similar DTC of subtracting (p=0.10), but their DTC of walking was significantly higher (p<0.0001). Conclusion: Given that walking on curved paths is considered more difficult than that on straight paths and that the serial subtracting dual task is more difficult than the box checking dual task, this study in older adults provides evidence for the existence of a (walking) situation-dependent change of prioritization. If confirmed in other studies, situation-dependent change of prioritization should be included as a potential factor contributing to gait and balance impairments, and increased fall risk in older adults.